2017
DOI: 10.3390/ijms18102214
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Review of Reactive Oxygen Species in Urological Cancer: Correlation with NADPH Oxidases, Angiogenesis, and Apoptosis

Abstract: Oxidative stress refers to elevated reactive oxygen species (ROS) levels, and NADPH oxidases (NOXs), which are one of the most important sources of ROS. Oxidative stress plays important roles in the etiologies, pathological mechanisms, and treatment strategies of vascular diseases. Additionally, oxidative stress affects mechanisms of carcinogenesis, tumor growth, and prognosis in malignancies. Nearly all solid tumors show stimulation of neo-vascularity, termed angiogenesis, which is closely associated with mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 158 publications
2
33
0
4
Order By: Relevance
“…Cells maintain a balance of ROS by means of the antioxidant system in physiological conditions (Torres et al, 2006). However, triggered by stress stimuli such as ionising radiation, chemotherapeutic drugs and viral infections, ROS can be excessively accumulated and regulate several pathological processes including proliferation, inflammation, autophagy and apoptosis (Circu and Aw, 2010;Miyata et al, 2017). Several studies showed that ROS participate in apoptosis induced by viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Cells maintain a balance of ROS by means of the antioxidant system in physiological conditions (Torres et al, 2006). However, triggered by stress stimuli such as ionising radiation, chemotherapeutic drugs and viral infections, ROS can be excessively accumulated and regulate several pathological processes including proliferation, inflammation, autophagy and apoptosis (Circu and Aw, 2010;Miyata et al, 2017). Several studies showed that ROS participate in apoptosis induced by viruses.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, uncontrolled generation of ROS as well as reactive nitrogen species (RNS) have been implicated in many diseases including cardiovascular disease, 3 arthritis, 4 neurodegenerative disease 5 and cancer. 6 With respect to cancer, ROS have been shown to be present at high concentrations in some types of cancers, due to the high metabolic activity of the cells. 7 ROS can cause modification of base pairs through abstraction or addition of hydrogen, induction of DNA strand breaks and DNA cross-linking causing DNA mutagenesis and initiating uncontrolled division, the initial step in tumour development.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…7 ROS can cause modification of base pairs through abstraction or addition of hydrogen, induction of DNA strand breaks and DNA cross-linking causing DNA mutagenesis and initiating uncontrolled division, the initial step in tumour development. 6 However, numerous studies have also concluded that increasing ROS levels can promote oxidative stress-induced cancer cell death. 8 Thus while the role of ROS in the prevention/induction of cancer is a topic of intense debate in general, the idea of using therapies which selectively generate oxidative stress in cancer cells was proposed as a possible therapeutic treatment for malignant cancers.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress in cancer cells plays a dual role: the generation of reactive oxygen species (ROS) in cells increases the proliferation and migration of cells and participates in the initiation and progression of PCa [1], but on the other hand, excessive ROS production induces DNA damage and triggers apoptosis [2]. Nuclear factor kappa-light-chain-enhancer of activated B cells (NFKB) signaling pathway is believed to be a link between inflammation and cancer, due to the induction of proliferation, blocking apoptosis in cells and maintaining angiogenesis [3], and the induction of oxidative stress with hypoxia inducible factor 1 alpha (HIF-1α) and estrogen receptor β (ERβ) [4].…”
Section: Introductionmentioning
confidence: 99%